Protein kinase B (AKT1) genotype mediates sensitivity to cannabis-induced impairments in psychomotor control. Issue 15 (November 2014) - Bhattacharyya, S.; Iyegbe, C.; Atakan, Z.; Martin-Santos, R.; Crippa, J. A.; Xu, X.; Williams, S.; Brammer, M.; Rubia, K.; Prata, D.; Collier, D. A.; McGuire, P. K.
<x content-type="archive" xml:space="preserve">Abstract</x> Background. What determines inter-individual variability to impairments in behavioural control that may underlie road-traffic accidents, and impulsive and violent behaviours occurring under the influence of cannabis, the most widely used illicit drug worldwide? Method. Employing a double-blind, repeated-measures design, we investigated the genetic and neural basis of variable sensitivity to cannabis-induced behavioural dyscontrol in healthy occasional cannabis users. Acute oral challenge with placebo or Δ9-tetrahydrocannabinol (THC), the main psychoactive ingredient in cannabis, was combined with functional magnetic resonance imaging, while participants performed a response inhibition task that involved inhibiting a pre-potent motor response. They were genotyped for rs1130233 single nucleotide polymorphisms (SNPs) of the protein kinase B (AKT1) gene. Results. Errors of inhibition were significantly (p = 0.008) increased following administration of THC in carriers of the A allele, but not in G allele homozygotes of the AKT1 rs1130233 SNP. The A allele carriers also displayed attenuation of left inferior frontal response with THC evident in the sample as a whole, while there was a modest enhancement of inferior frontal activation in the G homozygotes. There was a direct relationship (r = − 0.327, p = 0.045) between the behavioural effect of THC and its physiological effect in the inferior frontal gyrus, where AKT1 genotype modulated the effect of THC. Conclusions. These results require independent replication and show that differing vulnerability to acute psychomotor impairments induced by cannabis depends on variation in a gene that influences dopamine function, and is mediated through modulation of the effect of cannabis on the inferior frontal cortex, that is rich in dopaminergic innervation and critical for psychomotor control.